EPIDEMIOLOGY OF LIVER CIRRHOSIS AND ASSOCIATED COMPLICATIONS: CURRENT KNOWLEDGE AND FUTURE DIRECTIONS (World Bulletin of Public Health, 2025)
Liver cirrhosis is a progressive disease characterized by the irreversible scarring of the liver, leading to its functional impairment. It is a major global health concern due to its high morbidity, mortality, and the economic burden it imposes on healthcare systems. Cirrhosis can result from a variety of etiologies, including chronic viral hepatitis, alcohol use, non-alcoholic fatty liver disease (NAFLD), and autoimmune disorders. Understanding the epidemiology of cirrhosis and its associated complications is crucial for the development of effective preventive and therapeutic strategies. This article will review the current knowledge regarding the epidemiology of liver cirrhosis, the complications associated with it, and future research directions in the field
Keywords: TIPS; Xenotransplantation; magnetic resonance elastography